Assessment of fermented fish (ginamos) quality and its production practices in Culasi, Antique. - Caling, Marian Juliet Gochian
The study aimed to establish baseline data on the production process of ginamos, a fermented fish paste, in Culasi, Antique. This data determined the top producer and its ginamos product quality in terms of physicochemical properties, proximate composition, and microbiological quality. A purposive sampling to select 60 ginamos producers for the interview was employed. The study's respondents, primarily males aged 41-60 with diverse educational levels, have a blend of formal and informal ginamos production knowledge, a background in fishing, and adherence to hygiene and sanitation practices for ginamos making. Dulis (anchovy) caught from beach seines is used in fermentation. Producers vary in fish, salt, and sugar amounts and fermentation time ranging from 3 months to over a year. Ginamos are sold in oil containers with different pricing and annual sales quantities. Through the designed point-based system focused on hygiene knowledge and sales, three respondents stood out for their high sales volume and stringent hygiene practices, leading to their selection based on their scores. Physicochemical analysis indicated slight variations among ginamos samples in terms of pH (5.14 to 5.28), titratable acidity (1.88% to 2.36%), and sodium chloride content (15% to 20%). Proximate composition analysis showed moisture content ranging from 49.43% to 55.33%, fat between 0.92% and 1.42%, protein content from 24.28% to 31.38%, and ash content from 20.8% to 22.75%. These variations are attributed to individual producer characteristics and specific fermentation methods. In the survey, Producer 2, notable for cleanliness in production practices, had the highest hygiene score, with a total plate count of 2.83 x106 cfu/g and coliform of 9.5 x103 cfu/g, and no E. coli was detected. The low microbial load shows how rigorous hygiene affects product quality. Overall, differences in ginamos production practices highlight the necessity of standardized production methods for improved ginamos quality and safety. This provides scientific insights emphasizing the significance of hygiene and standardization in producing safer, high-quality ginamos.